Implications of Sundanese fathers’ parenting for the development of children's character - Wilodati, Wilodati; Wulandari, Puspita; Nur, Rezky Juniarsih (LPMPP Universitas Negeri Yogyakarta, 2025)
This study explores the implications of fathers’ parenting on children's character with a special focus on the integration of Sundanese cultural values such as cageur (healthy), bageur (good), bener (right), singer (introspective), and pinter (smart) in fostering children's character. This research was conducted using qualitative methods and phenomenological design. The focus of this research is Sundanese fathers who live in Bandung. The city of Bandung was chosen because its population is predominantly ethnic Sundanese. The research was conducted within a period of 6 months, from February to July 2024, and was preceded by preliminary studies on Sundanese fathers’ parenting patterns conducted since 2016. The participants in this study were Sundanese fathers whose wives are employed. In families where both parents are employed, this study describes their cooperation in childcare. The results of this study show that fathers' parenting in Sundanese families, which apply Sundanese cultural values such as cageur (healthy), bageur (good), bener (right), singer (introspective), and pinter (smart), have a significant impact on children's character development. Through the application of these values, fathers play an important role in supporting children's cognitive and social-emotional development, in accordance with the developmental theories of Jean Piaget and Erik Erikson. Authoritarian parenting can hinder children's cognitive and social-emotional development, while uthoritative parenting supports a balance between discipline and independence. Permissive parenting, in turn, tends to reduce children's discipline and responsibility. Overall, the integration of Sundanese cultural values in fathers' parenting not only shapes children's strong and stable character, but also supports holistic development that includes cognitive, social, and emotional aspects.